2010
DOI: 10.1002/cbf.1656
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of kisspeptin on liver oxidant and antioxidant systems in young male rats

Abstract: Kisspeptin is a recently discovered hypothalamic peptide which plays an important role in the central control of reproductive functions. We have investigated direct and indirect effects of kisspeptin on the liver oxidative stress in young male rats. Twenty-four rats were divided into four groups (n = 6/group). First group served as control and received saline. Kisspeptin-10 was administered to the animals in the second group (20 nmol/rat/day), for a period of 7 days. Rats were given only one dose gosereline (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 62 publications
2
25
0
Order By: Relevance
“…The KP peptide is known to increase catalase activity [18], which is also neuroprotective against A β [44]. The KP peptide also has thermoregulatory effects [19] and acts via nitric oxide in the facilitation of passive avoidance learning plus memory consolidation in vivo [17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The KP peptide is known to increase catalase activity [18], which is also neuroprotective against A β [44]. The KP peptide also has thermoregulatory effects [19] and acts via nitric oxide in the facilitation of passive avoidance learning plus memory consolidation in vivo [17].…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore likely that the mechanism for neuroprotection may involve an alternative process that is more likely receptor mediated. The in vivo actions of KP peptides include actions on the opioid system [12, 13], oxytocin/vasopressin systems [4, 14, 15], neurotransmitter systems [16, 17], activation of endogenous antioxidants [18], activation of nitric oxide [17], and effects on thermoregulation [19] that could be mediated via the prostaglandin systems [46, 47]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, measuring total oxidant and antioxidant capacities and making comparisons are much in use and practical today. Even TAC and TOC can be used in monitoring the treatment in use for a given disease or experimental study [44,45] . In the present study, TOC increased while TAC decreased in CCl 4 given animals as compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, the expression of kiss-I gene might relate to the increase of body weight and change with the high fat diets (Moral et al, 2011; Quennell et al, 2011). Kisspeptin might directly reduce the hepatic lipid peroxidation, preventing the negative effect of lipid peroxidation on intracellular regulatory mechanisms managing the release of hypothalamic hormones leading to defective neurotransmission (Aydin et al, 2010). However, these observations suggested that there is a relationship between kisspeptin and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%